Post-operative short-term clinical evaluation of direct lateral (Harding) approach in primary total hip replacement - Abdullah Abdulkareem Abbas; Ahmed Latteef Al-Shamari (Journal of the Pakistan Medical Association)
Objectives: To evaluate patients’ functional outcomes after total hip arthroplasty through a direct lateral approach.